IoT-Based Smart Waste System Using Blynk Application - Apdilah, Dicky (InfoTekJar : Jurnal Nasional Informatika dan Teknologi Jaringan, 2024)
The problem of manual trash cans causes a lack of hygiene for users and scattered garbage due to the volume of garbage bins that have accumulated. Paper and tissue waste is the dominant waste in the campus area and is highly flammable. Due to the lack of manual trash cans, innovation ideas were obtained to make automatic room trash cans and can monitor waste capacity and detect smoke using smartphone applications as the application of the Internet of Things (IoT). The IoT-based smart trash can uses the NodeMCU 8266 as its main control and ultrasonic sensors to detect the distance of the garbage capacity and the distance of the object. Servo motor as a drive for the garbage lid automatically. MQ-2 smoke sensor as a smoke marker, a warning sound through the Buzzer and also the Wifi ESP 8266 module so that it can send notifications via the internet network. Trash cans can be monitored using the Blynk application. The results obtained in this study are that the trash can cover will automatically open when the object is 10cm to 1cm from the trash can. The results of the sensor detection of the full capacity level of the waste are when the garbage is 5cm to 1cm from the sensor. Furthermore, the results of the detection of the MQ-2 sensor, when the smoke capacity exceeds 325ppm, the buzzer will turn on and the system sends a notification message using a Blynk to the cleaning staff's smartphone.